The Long, Lingering Shadow : Slavery, Race, and Law in the American Hemisphere - Cottrol, Robert J. (Book collections on Project MUSE., 2013)
Students of American history know of the law's critical role in systematizing a racial hierarchy in the United States. Showing that this history is best appreciated in a comparative perspective, The Long, Lingering Shadow looks at the parallel legal histories of race relations in the United States, Brazil, and Spanish America. Robert J. Cottrol takes the reader on a journey from the origins of New World slavery in colonial Latin America to current debates and litigation over affirmative action in Brazil and the United States, as well as contemporary struggles against racial discrimination and.